The Expected Holding Period Return, The Term Structure of Interest Rates and Investment in the Government of Canada Bond Market - McCallum, John S. (Journal of Finance, 1974)
John S. McCallum, The Expected Holding Period Return, The Term Structure of Interest Rates and Investment in the Government of Canada Bond Market, The Journal of Finance, Vol. 29, No. 1 (Mar., 1974), p. 276